Does the Decrease in Neutrophil-lymphocyte Ratio after BCG Treatment Be a Prognostic Marker for NMIBC? - Aykut Başer (Journal of Urological Surgery)

(untitled)
Objective:Non-muscle invasive bladder cancer (NMIBC) accounts for 75% of all bladder cancer cases. Several models to predict relapses and progression have been developed. We aimed to determine the predictive value of the neutrophil-lymphocyte ratio (NLR) for recurrence and/or progression of the disease.Materials and Methods:Seventy patients with high-risk NMIBC according to the European Organization for Research and Treatment of Cancer (EORTC) risk classification who were receiving Bacillus Calmette-Guerin (BCG) treatment and were followed up at our clinic were included in the study.Results:The average score level and NLR values differed significantly on patient classification according to the EORTC Progression and Recurrence Risk score. The positive correlations among EORTC Recurrence score, EORTC Progression score, Club Urológico Espanol de Tratamiento Oncológico (CUETO) Recurrence score, and CUETO Progression score and NLR values were not statistically significant. The NLR values decreased significantly on follow-ups on BCG treatment.Conclusion:Patients with bladder cancer have a high NLR, which has predictive utility with regard to prognosis. A decrease in NLR with BCG treatment is indicative of the decreased likelihood of recurrence and progression.